1994
DOI: 10.1007/bf02229882
|View full text |Cite
|
Sign up to set email alerts
|

Scleroderma renal crisis as a possible complication of cyclosporin a withdrawal

Abstract: The pharmacological treatment of systemic sclerosis (SSc) has been discouraging. In view of this, therapeutic trials with cyclosporine A (CyA) are outstanding particularly in patients with a rapid cutaneous involvement. We report the case of a patient whose SSc cutaneous manifestations dramatically improved with CyA therapy. Its subsequent withdrawal led to a quick onset of a fatal sclerodermal renal crisis. We believe that in our patient there could have been a cause and effect relationship between the suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It has been postulated that the ability of corticosteroids to inhibit prostacyclin production, which may result in increased ACE activity, contributes to the development of SRC. Scleroderma renal crisis has been reported in both hypertensive and nonhypertensive patients, 5,9,10,12,13,27 in patients already on ACE inhibitors, in patients without prior steroid treatment, in association with cyclosporine initiation, 28 in association with cyclosporine withdrawal, 4 after use of essential (volatile) oils, 17 and without antecedent factors. The vessel changes on kidney biopsy are similar to the microangiopathic abnormalities found on muscle biopsy in patients with MCTD and necrotizing myopathy.…”
Section: Discussionmentioning
confidence: 98%
“…It has been postulated that the ability of corticosteroids to inhibit prostacyclin production, which may result in increased ACE activity, contributes to the development of SRC. Scleroderma renal crisis has been reported in both hypertensive and nonhypertensive patients, 5,9,10,12,13,27 in patients already on ACE inhibitors, in patients without prior steroid treatment, in association with cyclosporine initiation, 28 in association with cyclosporine withdrawal, 4 after use of essential (volatile) oils, 17 and without antecedent factors. The vessel changes on kidney biopsy are similar to the microangiopathic abnormalities found on muscle biopsy in patients with MCTD and necrotizing myopathy.…”
Section: Discussionmentioning
confidence: 98%
“… 24 Finally, 27 review articles were excluded, and the remaining 37 identified primary research articles were included into the analysis. 24 60 The 37 articles consisted of 19 case reports, 15 case series, 1 open-label, randomized controlled trial with a no-treatment arm (group I iloprost vs group II iloprost with low-dose CsA), one open-label, prospective study with a historical control group (CSA group vs historical placebo group of the chlorambucil trial), 61 and one retrospective study without control (patients received prednisolone (0.5 mg/kg/d) and tacrolimus; Table 1 ).…”
Section: Results Of the Systematic Literature Searchmentioning
confidence: 99%
“…Altogether, hypertension was noticed in 13 patients. 26 , 31 33 , 36 , 42 , 48 , 59 Pathological renal biopsy was reported in 11 patients. 26 , 31 , 32 , 36 , 40 , 48 , 58 , 59…”
Section: Results Of the Systematic Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations